Cystic Fibrosis–related Liver Disease: Research Challenges and Future Perspectives. Issue 4 (October 2017) - Debray, Dominique; Narkewicz, Michael R.; Bodewes, Frank A.J.A.; Colombo, Carla; Housset, Chantal; de Jonge, Hugo R.; Jonker, Johan W.; Kelly, Deirdre A.; Ling, Simon C.; Poynard, Thierry; Sogni, Philippe; Trauner, Michael; et al.
ABSTRACT: Objectives: Hepatobiliary complications are a leading cause of morbidity and mortality in cystic fibrosis (CF) patients. Knowledge of the underlying pathological aspects and optimal clinical management is, however, sorely lacking. Methods: We provide a summary of the lectures given by international speakers at the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) monothematic conference on cystic fibrosis–related liver disease (CFLD) held in Paris in January 2016, to discuss the status of our current knowledge of liver disease in CF patients, to define the critical areas that need to be addressed, and to resolve actions to elucidate relevant mechanisms of disease to optimise future therapeutic options. Conclusions: The need for a universal consensus on the definition of CFLD to clarify disease stage and to identify relevant biomarkers to assess disease severity was highlighted. A deeper understanding of the pathophysiology and prognostic factors for the long-term evolution of CFLD is fundamental to move forward and has a strong bearing on identifying potential treatments. Novel experimental models and new treatment options under investigation are discussed and offer hope for the near future of CFLD. Abstract : Supplemental Digital Content is available in the text